Literasi Dakwah pada Akun Instagram @mubadalah.id tentang Pemahaman Kesetaraan Gender - Ilmiati, Tinta; Nurul Barkah, Fauzi; Tuahena, Rizky; Firmansyah, Nurizki (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This research is motivated by the lack of da'wah literacy in understanding gender equality on social media. The aim is to analyze da'wah literacy on the Instagram account @mujadalah.id related to the understanding of gender equality among users. The research method used is a content analysis study and content study to analyze posts related to gender equality. Research findings show that da'wah content on Instagram @mujadalah.id contributes to increasing awareness and understanding of gender equality. User response to the content varied, with most being supportive. This research also identifies challenges and opportunities in using social media as a means of preaching about gender equality, as well as the importance of education and ongoing dialogue to strengthen understanding and overcome stereotypes and prejudice that may arise. The results of this research can provide valuable insights for the development of communication strategies that are more effective and responsive to users' understanding and needs in the context of gender equality.